Resilience in Focus. Certain Mechanisms of the Deepening of the Economic and Monetary Union - Halmai, Péter (Public Finance Quarterly, 2021)
The economic resilience - the flexibility of the economy and also the capability of resistance to shocks - is a central category of European reform processes. It contains proactive and reactive dimension, as well as the necessity of adaptation to the new circumstances. The study examines the basic dimensions of resilience: vulnerability factors, shock absorption and the ability to recover, and finds that the efficiency of the interactions and synergy of the deep integration system is determined by the interconnected mechanisms of convergence and resilience. Approaching resilience may show a new direction to national economic policies. With the increase of resilience of certain member states, the structural reforms at national level could decrease (reduce) the expense of the anti-cyclical (national fiscal or common monetary) policies in stabilizing of the Eurozone’s economies.